European Union Priority Agenda Post-Covid 19 Pandemics In Security And Defense Sectors - Annisa Arjlia; Henny Saptatia Drajati Nugrahani (Journal of Social Research, 2024)
This research aims to explore and analyze the fundamental factors of the European Union's (EU) post Covid-19 priority agenda in the defense and security sector. The pandemic has shown that strengthening the defense and security sector to protect the country and its citizens from new threats is important and urgent for the European Union. The EU's post-pandemic priority agenda in the defense and security sector plays a crucial role in enhancing the defense and security capabilities of the European Union. This research focuses on five priority agendas, including: increasing military capacity, strengthening the European defense industry, enhancing cooperation among EU member states, improving cooperation with partner countries, and enhancing cybersecurity. This research seeks to answer the question of why it is important for the European Union to establish adjustment measures in the defense and security sector as a post-Covid-19 priority agenda and which programs are included in these five priority agendas. This research is a qualitative study that utilizes the European Security within the Constructivism paradigm proposed by Barry Buzan, Ole Waever , and Jaap de Wilde. This theory explains the dynamics of security in Europe and considers security a product of a complex social process that depends on the identities and norms present in the international community. In this theory, European identity is important in shaping European security. European identity is formed through historical and political processes that involve interactions and conflicts among European countries. Initial findings suggest that the EU's post- Covid-19 priority agenda in the defense and security sector is an effort to protect member states from external threats, but also to strengthen European identity in maintaining security.